2023
DOI: 10.1186/s12885-023-10657-0
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral immune cell profiling of double-hit lymphoma by mass cytometry

Abstract: Background Double-hit or Triple-hit lymphoma (DHL/THL) is a subset of high-grade B cell lymphoma harboring rearrangements of MYC and BCL2 and/or BCL6, and usually associate with aggressive profile, while current therapies tend to provide poor clinical outcomes and eventually relapsed. Further explorations of DHL at cellular and molecular levels are in demand to offer guidance for clinical activity. Methods We collected the peripheral blood of DHL p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Assessment of the healthy B cell pool of patients to find disease mechanisms [128] DLBCL Evaluation of the intertumoral and intratumoral heterogeneity [129] Identification of clinically relevant interactions between tumor-associated macrophages and blood endothelial cells [130] Finding proteins overexpressed in relapsed and refractory patients [131] Comparison of major immune subsets in DLBCL and double-hit lymphoma [132] Identification of differences in immune cell compartments across various stages of MM and healthy individuals [133] Description of the immune tumor microenvironment in patients with MGUS and MM at diagnosis and post-initial therapies [134] Analysis of the immune checkpoint signature and regulation [135] Characterization of NK cells in newly diagnosed cases [136] Understanding of the molecular and cellular complexities underlying disease heterogeneity and prognosis [137] Provision of insights into the mechanism of action of daratumumab and the anti-PD-L1 monoclonal antibody atezolizumab [138] MM Employment of protein profiling as a tool for prognosis and treatment stratification [139] Other Tools RRPA CLL Prediction of survival outcomes based on the proteomic signature [140] Protein Microarrays FL Identification of antibodies that distinguish lymphoid follicles in FL and benign follicular hyperplasia [141] MCL Monitoring of patient serum proteomes to identify treatment-modulated proteins linked to the presence of minimal residual disease [142] Western Blot MCL Definition of the pathologic hallmark of MCL as a tool for the diagnosis [143] araCTP, Next, we describe the basis of the main protein-based strategies employed for studying B cell malignancies.…”
Section: Analysis Of the Tumor Microenvironment To Find Differences I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of the healthy B cell pool of patients to find disease mechanisms [128] DLBCL Evaluation of the intertumoral and intratumoral heterogeneity [129] Identification of clinically relevant interactions between tumor-associated macrophages and blood endothelial cells [130] Finding proteins overexpressed in relapsed and refractory patients [131] Comparison of major immune subsets in DLBCL and double-hit lymphoma [132] Identification of differences in immune cell compartments across various stages of MM and healthy individuals [133] Description of the immune tumor microenvironment in patients with MGUS and MM at diagnosis and post-initial therapies [134] Analysis of the immune checkpoint signature and regulation [135] Characterization of NK cells in newly diagnosed cases [136] Understanding of the molecular and cellular complexities underlying disease heterogeneity and prognosis [137] Provision of insights into the mechanism of action of daratumumab and the anti-PD-L1 monoclonal antibody atezolizumab [138] MM Employment of protein profiling as a tool for prognosis and treatment stratification [139] Other Tools RRPA CLL Prediction of survival outcomes based on the proteomic signature [140] Protein Microarrays FL Identification of antibodies that distinguish lymphoid follicles in FL and benign follicular hyperplasia [141] MCL Monitoring of patient serum proteomes to identify treatment-modulated proteins linked to the presence of minimal residual disease [142] Western Blot MCL Definition of the pathologic hallmark of MCL as a tool for the diagnosis [143] araCTP, Next, we describe the basis of the main protein-based strategies employed for studying B cell malignancies.…”
Section: Analysis Of the Tumor Microenvironment To Find Differences I...mentioning
confidence: 99%
“…A broader immune characterization was performed using a 42-marker CyTOF panel, describing the relative frequencies of major immune subsets (i.e., B cells, T cells, and monocytes) [132]. In this study, the authors aimed to find differences between DLBCL and DHL (double-hit lymphoma), an aggressive high-grade B cell lymphoma presenting rearrangements of MYC and BCL2 genes.…”
Section: Proteomics Studies On Diffuse Large B Cell Lymphoma (Dlbcl)mentioning
confidence: 99%
“… 14 Studies on small sets of patients with MYC -rearranged lymphoma reported decreased CD3 + T cells compared with healthy donors (HDs) 15 and higher frequencies of CD4 + CD8 + T cells and γδ T cells than patients with DLBCL NOS but a lower ratio of immunosuppressive CD4 – CD8 – T-cells. 16 However, studies extensively investigating the impact of oncogenic MYC on phenotype and functionality of circulating immune effector cells in patients with HGBL- MYC/BCL2 vs those with DLBCL NOS are lacking. In light of current and emerging T-cell– and NK cell–based immunotherapeutic approaches, we performed comprehensive flow cytometry–based profiling of circulating peripheral blood T cells and NK cells from a large cohort of newly diagnosed patients with HGBL- MYC/BCL2 and compared them with newly diagnosed patients with DLBCL NOS without a MYC rearrangement and age-matched HDs.…”
Section: Introductionmentioning
confidence: 99%